Pengembangan Sistem Tiket Kereta Berbasis Visual Basic dengan Integrasi dan Pengujian Database - Pratama, Bintang Arya Putra; Yandi, Khoiru Alfi Syahri; Basatha, Rizky (Lembaga Yasin AlSys, 2025)
This study aims to develop a train ticketing system based on Visual Basic integrated with a database to enhance efficiency and accuracy in ticket booking management. The system is designed to simplify the ticket booking process, centralize data storage, and streamline information management. The development methodology includes system requirements analysis, user interface design, and database implementation using Microsoft Access as the data storage medium. The system was tested using black-box testing to evaluate its functionality and reliability. The test results show that the system effectively manages ticket booking data, reduces input errors, and provides users with easy access. With stable database integration, this system is expected to support improved services in the railway transportation industry.